(3YeOI GdCMcGes - (3GdbQTj, GdebOSj, GdLnqeGYjdj, Ke GdOeTbj, GHf bOGeI, YHO Gddg Hf eMeO Hf bOGeI, (B620 (3g`s ((3CMeO Hf jhSa Hf LGHQ Hf YHO Gddgs)
(3ChdgG (B:s
(3GdMeO ddg Cgd GdMeO heSJMbg MeOG jaVd Ydi cd MeO caVd Gddg Ydi Ndbgs
(3BNQgG (B:s
(3Ke GOYGgG GdBNQ aUOb GdGHf agj ddChd hdG TjA ddKGfj hjZQegG dg dCfg ahJgG Ydjg HEbQGQg hGddg CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 67s
(3eYLe GdeDdajf (B2 / 227s
(3cTa GdXfhf (B2 / 1164s
(3TPQGJ GdPgH (B5 / 88s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs